Corruption as a Valence: The Paradox of Electorate Punishment of Political Parties in Indonesia - Wasisto, Aryo; Mulyadi, Mohammad; Doly, Denico; Budi Prihatin, Rohani; Moenek, Reydonnyzar (International Journal of Psychosocial Rehabilitation, 2020)
This article discusses corruption as a valence issue that has not been enough to delegitimize corrupt parties. Delegitimation of corrupt parties in Indonesia does not run significantly. By using a qualitative approach, this article explores, as well as understanding the issue of corruption that has not been able to delegitimize political parties. This descriptive research aims to explain the symptoms and current events. By interviewing people who understand corruption supplemented with the input of literature studies, this article generates the idea that the relationship between corruption and delegitimation in Indonesia is paradoxical. In reality, people still won corrupt parties. This article also examines people’s viewpoints on corruption by analyzing their political closeness. This article sorts out the different levels of each group based on its affinity to political party institutions (1) supporters or officers of political parties tended to tolerate the party that they supported, and (2) pragmatic groups who were confused in political spectrums but decided only to get benefits. (3) apathetic groups did not pay attention to the political system but were disaffected by corruption activity; last (4), anti-corruption societies actively promoted better corruption eradication.